Model Aplikasi Sistem Informasi Akuntansi Realisasi Anggaran Pada SMAN 1 Banjaran - Regine Berlian Pratama (Labkat Press KA FTIK UNIKOM, 2018)
SMAN1 Banjaran which is addressed at Jl. Ciapus No. 7 Bandung Regency is educational institution. At the time of conducting the research, the researcher found the Administration section where there was a treasurer and so on. At SMAN 1 Banjaran it has been computerized, namely by using Microsoft Excel and Word but has not used hyperlink facilities, so that there is a repeat input process. And in making financial reports that are still not in accordance with existing standards. The researcher conducts research in the financial section, namely in the part of the BOS Fund (Student Operational Assistance). So the researcher conducted a study entitled